Proximal Esophageal Stenosis in Head and Neck Cancer Patients after Total Laryngectomy and Radiation - Vu, Kim N. (ORL J Otorhinolaryngol Relat Spec, 2008)
BACKGROUND: There has been an increasing focus on late functional effects of head and neck cancer (HNC) treatment. This study was undertaken to evaluate the incidence of late proximal esophageal stricture in patients undergoing total laryngectomy (TL) and radiation therapy (RT). MATERIAL AND METHODS: An institutional retrospective review of HNC patients treated between 1995 and 2003 with TL and RT was undertaken. Thirty-three patients with stage II–IV disease were included; 25 patients had TL and postoperative RT (group 1), while 8 patients had definitive RT with salvage laryngectomy (group 2). RESULTS: The median follow-up was 28 months. At the last follow-up, 25 patients (76%) were alive and disease free. Four had died and 3 developed distant metastasis. Dysphagia or stenosis developed in 40% in group 1 and 75% in group 2 patients. The median time to dysphagia was 5.5 months for all patients. CONCLUSIONS: The incidence of esophageal stenosis was 33% for all patients. Contributing factors for esophageal stenosis after TL and RT include continued alcohol and tobacco use, the dose-volume relationship of the RT and normal tissue damage from the tumor and the treatment.